2015
DOI: 10.4161/15384101.2014.980631
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 mediates cell cycle arrest in S phase through non-structural protein 3D

Abstract: Many viruses disrupt the host cell cycle to facilitate their own growth. We assessed the mechanism and function of enterovirus 71 (EV71), a primary causative agent for recent hand, foot, and mouth disease outbreaks, in manipulating cell cycle progression. Our results suggest that EV71 infection induces S-phase arrest in diverse cell types by preventing the cell cycle transition from the S phase into the G2/M phase. Similar results were observed for an alternate picornavirus, Coxsackievirus A16. Synchronization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 49 publications
12
73
2
Order By: Relevance
“…Many investigators have tried to inhibit the activity of 3D protein and thereby inhibit viral replication [30, 47, 48]. It is also involved in the regulation of cell S-phase arrest [49] and immune response [50]. However, the role of 3D in the regulation of NLRP3 inflammasome has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have tried to inhibit the activity of 3D protein and thereby inhibit viral replication [30, 47, 48]. It is also involved in the regulation of cell S-phase arrest [49] and immune response [50]. However, the role of 3D in the regulation of NLRP3 inflammasome has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of viral replication in an arrest state has also been reported for other RNA viruses (32,50); however, the specific mechanisms by which this enhancement occurs remain unclear. While we have demonstrated that induction of an S-phase arrest state leads to increased ZIKV protein expression, RNA levels, and titers, we have not yet explicitly determined at which stage of the viral life cycle this enhancement occurs.…”
Section: Discussionmentioning
confidence: 74%
“…Influenza A virus induces favorable conditions for viral protein accumulation and virus production by inducing G 0 /G 1 cell cycle arrest in infected cells (45). Enterovirus 71 mediates cell cycle arrest in S phase through its nonstructural protein 3D (46). HIV-1 Vif protein promotes the G 1 /S transition to promote infection and latency (47).…”
Section: Discussionmentioning
confidence: 99%